Reduction of Aldehydes and Ketones to Corresponding Alcohols Using Diammonium Hydrogen Phosphite and Commercial Zinc Dust - K. Anil Kumar; D. Channe Gowda (E-Journal of Chemistry)
A mild and an efficient system has been developed for the reduction of aromatic aldehydes and ketones to their corresponding alcohols in good yield using inexpensive commercial zinc dust as catalyst and diammonium hydrogen phosphite as a hydrogen donor.